Bribery and Justice in Exodus 23:1–9: Implications for Anti-Corruption Frameworks in Indonesia - Sukanto Limbong; Daniel Razsekar Panjaitan (Civiliza Publishing, 2026)
This article examines the prohibition of bribery and the mandate for impartial justice in Exodus 23:1–9, exploring its theological-ethical foundations and implications for anti-corruption frameworks in Indonesia. Employing literary-rhetorical analysis and contextual hermeneutics, the study investigates the pericope's chiastic structure, legal setting, and Hebrew terminology—particularly šōḥad (bribe) and ṣedeq (justice). The findings demonstrate that the text reframes bribery not as a procedural violation but as a theological offense that distorts judicial perception, subverts righteousness, and fractures communal integrity. Uniquely, the injunction is anchored in Israel's collective memory of Egyptian oppression (v. 9), grounding justice in empathetic solidarity—a dimension largely absent from modern anti-corruption discourse. The article contends that Exodus 23:1–9 offers a robust ethical paradigm for reinvigorating anti-corruption efforts in Indonesia, providing moral resources for reinforcing judicial integrity, protecting the vulnerable, and fostering ethical formation among public officials. By bridging biblical ethics with contemporary governance challenges, this study demonstrates that the ancient text's vision of justice—rooted in impartiality, compassion, and collective memory—constitutes a transformative framework for addressing systemic corruption in Indonesia's judicial institutions.